Failure Analysis of Induced Draft Fan Bearing in PT Semen Padang Using The RCM Method - Rozi Saferi; Sulaeman; Olka Defra Wanda (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2023)
The development of the technology is getting trigger competition in industri. To compete, companies should can provide products and the quality of services best for consumer. This study aims to find out the causes of bearings that are damaged in the Induced Draft Fan (IDF Bearing) and how to plan strategic maintenance of IDF Bearing. The method used is reliability centered maintenance (RCM). The causes of bearing damage are analyzed using the Failure Mode Effect and Critical Analysis (FMECA) method. The results of this study show that the cause of IDF Bearing damage is clearance with an RPN value of 210, lubrication system with an RPN value of 36, unbalance with an RPN value of 72, and high temperature with an RPN value of 54. Scheduled Restoration Maintenance is applied for IDF Bearing , where task or preventive maintenance in the form of oil change with a time of 5803.2 hours or 241 days.